2011
DOI: 10.1002/pssb.201100615
|View full text |Cite
|
Sign up to set email alerts
|

Extensions of DFTB to investigate molecular complexes and clusters

Abstract: International audienceMolecular complexes and clusters provide bridges between molecular and solid states physics. Containing tens to few thousands of atoms, such systems can hardly be approached via traditional ab initio wavefunction based methods at the moment. Density functional theory (DFT) and density functional based tight binding methods (DFTB) have strongly developed with respect to computational efficiency to cover this size range. However both DFT and currently implemented DFTB face difficulties to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 220 publications
(274 reference statements)
0
31
0
Order By: Relevance
“…The initial decrease of the dissociation energies with size is due to the dilution of the attractive interaction due to resonance charge. Indeed, as shown by the CI-DFTB calculations, there is a strong charge resonance effect in small clusters up to sizes n=4-5, namely as already mentioned the charge may extend over up to three units [32,35,88]. Actually, the cohesive energies of small clusters between 2 and 7 units vary in the range [0.25-0.62 eV] for neutrals and in the range [0.54-0.76 eV] for cations, illustrating the reinforced stability of the small cation clusters [35,51].…”
Section: Discussionmentioning
confidence: 52%
“…The initial decrease of the dissociation energies with size is due to the dilution of the attractive interaction due to resonance charge. Indeed, as shown by the CI-DFTB calculations, there is a strong charge resonance effect in small clusters up to sizes n=4-5, namely as already mentioned the charge may extend over up to three units [32,35,88]. Actually, the cohesive energies of small clusters between 2 and 7 units vary in the range [0.25-0.62 eV] for neutrals and in the range [0.54-0.76 eV] for cations, illustrating the reinforced stability of the small cation clusters [35,51].…”
Section: Discussionmentioning
confidence: 52%
“…24 To this end, we used an empirical dispersion term and a correction for the Coulomb interaction in which the Mulliken charges are replaced by the Class IV – Charge Model 3 developed in the context of DFT 25 and later introduced in the SCC-DFTB potential. 26 The importance of including such terms to accurately describe molecular aggregates was demonstrated by Simon and co-workers, in particular, these authors showed that they lead to accurate results for water molecule aggregates. 27 Jahangiri et al also showed that the SCC-DFTB model and its extensions provide reliable results for the structure, energetics, charge distributions, and vibrational spectral of various hydrogen-bonded systems.…”
Section: Methodsmentioning
confidence: 99%
“…24 The SCC-DFTB approach requires additional corrections to properly deal with weak intermolecular interactions. 26 To this end, we used an empirical dispersion term 29 and a correction for the Coulomb interaction in which the Mulliken charges are replaced by the class IV – Charge Model 3 developed in the context of DFT 25 and later introduced in the SCC-DFTB potential. 30 In all our calculations, the self-consistent process is stopped when the largest atomic charge fluctuation is smaller than 10 –8 a.u.…”
Section: Methodsmentioning
confidence: 99%
“…Among the available options, the Density-Functional based Tight-Binding method (DFTB) is considered as a state-of-the-art parameterized method [54,55,56,57,58,59]. It is derived from DFT via several approximations and has proved to be particularly efficient for the description of complex molecular systems [60,61,62,63]. Its accuracy depends significantly on the quality of the parameterization.…”
Section: Introductionmentioning
confidence: 99%